Genotypic and Phenotypic Characteristics of 29 Patients With Rare Types of Osteogenesis Imperfecta: Average 5 Years of Follow-Up - Xi, Lei; Zhang, Hao; Zhang, Zhen-Lin (Frontiers in Genetics, 2021)
Osteogenesis imperfecta (OI) is a rare genetic disorder characterized by bone fragility and abnormal connective tissue. Ninety percent of OI patients are caused by two mutations of COL1A1 and COL1A2, and more investigation was needed to better understand the rare types of OI. We followed up 29 patients with rare types of OI for an average of 5.4 years, and genotype, height, bone mineral density (BMD), blood biochemical indexes, misdiagnosis, and fracture were recorded. IFITM5 gene mutation was found in 18 patients (62.1%), which represents the most common pathogenic gene of rare types of OI in Chinese population. Thirteen cases had once been misdiagnosed, and the initial misdiagnosis rate was 44.8% (13/29). The higher misdiagnosis rate should be paid attention to by clinicians and healthcare providers, and we also give corresponding suggestions. Compared with the non-bisphosphonate treatment group, patients treated with bisphosphonates had higher lumbar spine BMD, fewer fractures, and lower levels of β-CTX and osteocalcin. However, there was no significant difference between OI type V patients and non-type V patients. Our study enriched the knowledge of genotype and phenotype characteristics of OI patients with rare types and bisphosphonate therapy.